The Five-item Modified Frailty Index is Predictive of 30-day Postoperative Complications in Patients Undergoing Spine Surgery. Issue 14 (15th July 2021) - Pierce, Katherine E.; Naessig, Sara; Kummer, Nicholas; Larsen, Kylan; Ahmad, Waleed; Passfall, Lara; Krol, Oscar; Bortz, Cole; Alas, Haddy; Brown, Avery; Diebo, Bassel; Schoenfeld, Andrew; et al.
Abstract : Study Design: Retrospective cohort study. Objective: This study aimed to evaluate the utility of the modified frailty index (mFI-5) in a population of patients undergoing spine surgery. Summary of Background Data: The original modified frailty index (mFI-11) published as an American College of Surgeons National Surgical Quality Improvement Program 11-factor index was modified to mFI-5 after variables were removed from recent renditions. Methods: Surgical spine patients were isolated using current procedural terminology codes. mFI-11 (11) and mFI-5 (5) were calculated from 2005 to 2012. mFI was determined by dividing the factors present by available factors. To assess correlation, Spearman rho was used. Predictive values of indices were generated by binary logistic regression. Patients were stratified into groups by mFI-5: not frail (NF, <0.3), mildly frail (MF, 0.3–0.5), severely frail (SF, >0.5). Means comparison tests analyzed frailty and clinical outcomes. Results: After calculating the mFI-5 and the mFI-11, Spearman rho between the two indices was 0.926( P < 0.001). Each index established significant (all P < 0.001) predictive values for unplanned readmission (11 = odds ratio [OR]: 5.65 [2.92–10.94]; 5 = OR: 3.68 [1.85–2.32]), post-op complications (11 = OR: 8.56 [7.12–10.31]; 5 = OR: 13.32 [10.89–16.29]), and mortality (11 = OR: 41.29 [21.92–77.76]; 5 = OR: 114.82 [54.64–241.28]). Frailty categories by mFI-5 were: 83.2% NF, 15.2% MF, and 1.6% SF. From 2005 to 2016, rates of NF decreased (88.8% to 82.2%, P < 0.001), whereas MF increased (9.2% to 16.2%, P < 0.001), and SF remained constant (2% to 1.6%, P > 0.05). With increase in severity, postoperative rates of morbidities and complications increased. Conclusion: The five-factor National Surgical Quality Improvement Program modified frailty index is an effective predictor of postoperative events following spine surgery. Severity of frailty score by the mFI-5 was associated with increased morbidity and mortality. The mFI-5 within a surgical spine population can reliably predict post-op complications. This tool is less cumbersome than mFI-11 and relies on readily accessible variables at the time of surgical decision-making. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textWith use of the five-factor modified frailty index within a surgical spine population, post-op complications can be reliably predicted. This tool is less cumbersome than the original 11-factor modified frailty index and relies on readily accessible variables available at the time of surgical decision-making.